Analysis of selected toxic metals using bacterial biosensors and their macromolecular derivatives - Bartos, Adrian (Wydawnictwo Politechniki Łódzkiej, 2012)
This short review presents a number of bacterial transcription mechanisms dependant on metal occurrence in growth environment. Metallic ions such as mercury, cadmium or zinc evoke genetic response, which then can be engineered and utilized to reprogram cells. Recombinant biosensors could be applied in detection and quantification of trace amounts of toxic metals. The article presents a few examples of such use and also touches upon other related approaches where sensitivity to metals was a backbone for an idea to measure metal concentrations.